Implementation of Performance Management at State Junior High School 4 Tanjungpinang - Anisha Avazura; Doni adrian; Kurnia Herwandi; Wiwi Winanda Nur; Satriadi Satriadi (International Journal of Management Research and Economics, 2024)
The implementation of performance management is a key factor that affects the level of success, so it is important to identify performance management indicators at SMP Negeri 4 Tanjungpinang. This study aims to identify various factors related to the performance of SMP Negeri 4 Tanjungpinang staff from the principal to the teachers, such as curriculum, competencies, strategies, constraints faced, assessment systems, and performance measurement. This research methodology uses a qualitative approach with interviews as a data collection tool. The data collected from these interviews were analyzed using content analysis techniques. The analysis results of this study provide valuable information for SMP Negeri 4 Tanjungpinang to improve the quality of performance. The population of this study were 58 organizational structures with a sample of 1 principal of SMP Negeri 4 Tanjungpinang.